Long-term progression-free survival with first-line pyrotinib monotherapy in a treatment-naïve stage IV NSCLC patient harboring an ERBB2 exon 20 insertion: a case report - Ke, Zhenyu; Yang, Hongbo; Xing, Meng; Bi, Shasha; Yang, Fujun (Frontiers in Oncology, 2025)
HER2 (ERBB2) mutations, particularly exon 20 insertions, are rare but actionable oncogenic drivers in non-small cell lung cancer (NSCLC). Pyrotinib, an oral irreversible pan-ErbB tyrosine kinase inhibitor, has shown promising efficacy in previously treated HER2-mutant NSCLC, but its role in the first-line setting remains unclear. We report a case of a 61-year-old woman with stage IVB lung adenocarcinoma harboring an ERBB2 exon 20 insertion (p.Y772_A775dup) and a concurrent EGFR mutation, who was treated with first-line pyrotinib monotherapy. She achieved a partial response within one month and has maintained disease control for over 31 months, with only mild intermittent diarrhea. This case provides real-world evidence supporting the potential of pyrotinib as an effective first-line treatment for HER2-mutant NSCLC, particularly in patients with the Y772_A775dup variant and concurrent EGFR alterations, and highlights the need for further clinical investigation in this setting.